1966
DOI: 10.1093/jee/59.6.1363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Radiation on Rhyzopertha dominica, Sitophilus oryzae, Tribolium confusum, and Lasioderma serricorne

Abstract: _ -1973 : Comparative gamma radiation sensitivity of Tribolium madens and T . castaneum. J. Stored Prod. Res. 9,93-100. BROWN, G. A.; BROWER, J. H.; TILTON, E. W., 1972: Gamma radiation effects on Sitophilus Zea mais and S. granarius. J. Econ. Ent. 65, 203-205. COGBURN, R. R., 1967: Infra red radiation effects on reproduction of three species of stored products insects. J. Econ. Ent. 60, 548-550. -BROWER, J. H.; TILTON, E. W., 1971: Combination of gamma and infra red gamma radiation for control of the Angoumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 0 publications
3
12
1
1
Order By: Relevance
“…Eggs and larvae were the least tolerant of radiation, which is consistent with the results of other studies that have reported increasing tolerance to radiation as life-stage development progresses (Follett 2008;Tilton et al 1966;Wang et al 2006;Yoshida et al 1974;Zhan et al 2011b). Larval and pupal development was arrested following treatment at all doses tested (75 to 175 Gy).…”
Section: Effectiveness Of Ionising Radiation As a Sterility Treatmentsupporting
confidence: 90%
See 2 more Smart Citations
“…Eggs and larvae were the least tolerant of radiation, which is consistent with the results of other studies that have reported increasing tolerance to radiation as life-stage development progresses (Follett 2008;Tilton et al 1966;Wang et al 2006;Yoshida et al 1974;Zhan et al 2011b). Larval and pupal development was arrested following treatment at all doses tested (75 to 175 Gy).…”
Section: Effectiveness Of Ionising Radiation As a Sterility Treatmentsupporting
confidence: 90%
“…We recognise the limitations of the data presented here; however, our results provide an indication of an upper limit to an effective dose, taking account of the widely reported increase in tolerance to ionising radiation within a species as a function of increasing development stage (Follett 2008;Tilton et al 1966;Wang et al 2006;Yoshida et al 1974;Zhan et al 2011b). All adult H. ligniperda were sterile following irradiation at 175 Gy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A similar phenomenon has been observed in diverse species of stored product insects (16). TILTON et al (7) described the minimum sterilizing dose of gamma ray as 250 and 175 Gy for males and females, respectively, which was a little higher than our results for X-ray. RAHIM and NORIMAH (11) described the minimum dose as 0.1 kGy when both parents were exposed, which is identical to our finding.…”
Section: Discussioncontrasting
confidence: 80%
“…Since the 1950s, the effect of ionizing radiation from another source, i.e., gamma ray from 60 Co, has been investigated. Lethal and sterilizing doses were confirmed (7)(8)(9)(10)(11)(12)(13)(14), but gamma-ray irradiation has not been applied industrially for disinfestation of tobacco, perhaps partly due to the lack of consumer acceptance. Recently high-energy electron beam accelerators have been developed and converted X-ray generated by the accelerators became industrially available as a reliable and safer source of ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%